Crystal structure of Arabidopsis DWARF14‐LIKE2 (DLK2) reveals a distinct substrate binding pocket architecture. (13th September 2022) - Bürger, Marco; Honda, Kaori; Kondoh, Yasumitsu; Hong, Sharon; Watanabe, Nobumoto; Osada, Hiroyuki; Chory, Joanne
Abstract: In Arabidopsis thaliana, the Sigma factor B regulator RsbQ‐like family of α/β hydrolases contains the strigolactone (SL) receptor DWARF14 (AtD14), the karrikin receptor KARRIKIN INSENSITIVE2 (AtKAI2), and DWARF14‐LIKE2 (AtDLK2), a protein of unknown function. Despite very similar protein folds, AtD14 and AtKAI2 differ in size and architecture of their ligand binding pockets, influencing their substrate specificity. We present the 1.5 Å crystal structure of AtDLK2, revealing the smallest ligand binding pocket in the protein family, bordered by two unique glycine residues. We identified a gatekeeper residue in the protein's lid domain and present a pyrrolo‐quinoline‐dione compound that inhibits AtDLK2's enzymatic activity.